Syzygium polyanthum protects against diabetic cardiac apoptosis in the chronic diabetes mellitus - Sari, Flori R; Hendarto, Hari; Adhiyanto, Chris; Ananditya, Fadhlurrahman; N, Irfiani; Rifa, Alissa; Syabrina, Fheby; Nadira, -; Ajizah, Putri Rahma (International Journal of Human and Health Sciences (IJHHS), 2020)
Introduction: Hyperglycemia has become the main characteristic of diabetes mellitus. Persistent hyperglycemia directly activates cell death pathway that plays pivotal role in the diabetic complication including diabetic cardiomyopathy. Syzygium polyanthum plays a beneficial role in the diabetic condition by reducing the blood glucose concentration, however the role of this natural resources in preventing further complication of diabetes mellitus has not been revealed fully yet. Method: Syzygium polyanthum dry extract (300 mg/kg body weight) were given daily for 28 days in the streptozotocin-induced diabetic rat. Measurement of blood glucose concentration were done three times during the study, meanwhile cholesterol concentration, myocardial diameter and cardiac apoptosis were measured on the day 28 of the study. Cardiac apoptosis was analyzed by the TdT-mediated dUTP nick end-labelling (TUNEL Assay). Results: Persistent hyperglycemia as well as cardiac apoptosis was significantly observed in the diabetic rat (D) on the day 28 of the study confronted to the normal rat (N). Interestingly, significant blood glucose reduction in concomitant with a lesser concentration of cardiac apoptosis were observed in the diabetic rat received 28 days Syzygium polyanthum extract (DS) confronted to the D rat. Additionally, lower plasma cholesterol concentration was significantly observed in the DS rat confronted to the D rat. Discussion: Significant cardiac apoptosis was observed in consistent with persistent hyperglycemia in the D rat as well as lesser cardiac apoptosis was observed in accordance with blood glucose concentration reduction in the DS rat. Therefore, Syzygium polyanthum may play beneficial role in the diabetic-associated cardiac apoptosis through its direct effect on the blood glucose concentration reduction. However further analysis should be done to fully elucidate the apoptotic pathway that involved. International Journal of Human and Health Sciences Vol. 05 No. 01 January’21 Page: 16-21